PENGGUNAAN BAHASA PADA REKLAME DAN PAPAN IMBAUAN PUBLIK DI KECAMATAN NGABANG KABUPATEN LANDAK - Veronika Damaria; Ahmad Rabi’ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2022)
AbstractResearch on the use of language in billboards and public notice boards in Ngabang District, Landak Regency focuses on billboards, posters, and banners. Things to consider consist of physical variables, language variables, legal variables. This aspect determines the criteria for the linguistic situation of outdoor media in the area based on the assessment instrument. This research uses descriptive and qualitative methods. The research data are written, physical and language positions on billboards and public notice boards. The research data sources, namely billboards and public notice boards in Ngabang District, consist of 3 objects, namely billboards, posters, and banners. The data collection technique used is the documentation technique. The amount of data collected in this study was 44 data, 44 data were classified into 3 groups of research objects of billboards and public notice boards in the form of billboards, posters, and banners and analyzed based on physical variables, language variables, and legal variables were scored based on the assessment instrument. Based on the calculation of the data score on the assessment of the criteria for the linguistic situation of billboards and public notice boards in Ngabang District, the score was 223.5. These results determine that the billboards and public notice boards in Ngabang Sub-district are included in the criteria for controlled area III, namely areas where the use of foreign languages is quite controlled by prioritizing the use of Indonesian or regional languages.Keywords : Advertisement, Ngabang District, Public Appeal Board, Use of Languange